2022
DOI: 10.1007/s00468-022-02349-2
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the role of dragon’s blood in the undisturbed growth of dragon trees

Abstract: Key message Dragon’s blood secretion is an integral part of the normal development of the leaves and of the tissue protecting the trunk of dragon trees. Abstract Dragon’s blood is a common name of a red resin produced in response to wounding by tree-like monocot species of the genus Dracaena (Asparagaceae), known as dragon trees. This resin has important medicinal uses and economic value. However, its ecological significance and mechanism of secretion are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…(2020) have suggested that the major chemical constituents of dragon’s blood are transported out of the intracellular space in response to various stimuli by three potential transport mechanisms i.e., vesicle trafficking mediated transport, GST (glutathione S-transferase) transport or membrane transport. Recent studies of the leaf shedding of dragon trees have shown that dragon’s blood is in the form of vesicles, which have a tendency to aggregate and fill the cells or intercellular spaces ( Jura-Morawiec et al., 2023 ). After the injury of the secondary tissues, resin typically fills the parenchyma cells and enters tracheids through the pits occluding their lumen ( Cui et al., 2013 ; Jura-Morawiec and Tulik, 2015 ; Xu et al., 2022 ; Figure 1B ).…”
Section: Resin-secreting Cells In the Secondary Growth Of Monocotyled...mentioning
confidence: 99%
“…(2020) have suggested that the major chemical constituents of dragon’s blood are transported out of the intracellular space in response to various stimuli by three potential transport mechanisms i.e., vesicle trafficking mediated transport, GST (glutathione S-transferase) transport or membrane transport. Recent studies of the leaf shedding of dragon trees have shown that dragon’s blood is in the form of vesicles, which have a tendency to aggregate and fill the cells or intercellular spaces ( Jura-Morawiec et al., 2023 ). After the injury of the secondary tissues, resin typically fills the parenchyma cells and enters tracheids through the pits occluding their lumen ( Cui et al., 2013 ; Jura-Morawiec and Tulik, 2015 ; Xu et al., 2022 ; Figure 1B ).…”
Section: Resin-secreting Cells In the Secondary Growth Of Monocotyled...mentioning
confidence: 99%